Application of the IoT concept and open-source platforms for condition monitoring of low voltage electrical panels - Artur, Matheus Damaceno; Belchior, Fernando Nunes; Rabelo, Diogo de Souza; de Souza, Danilo Augusto Santana; Francisco, Roberto da Piedade; Hunt, Julian David (Latin American Journal of Energy Research, 2026)
In an increasingly dynamic, complex and competitive market, an adequate maintenance strategy is essential for companies to get their processes and equipment operating safely and reliably, in aiming to meet quality requirements and reduce overall costs. In this assumption, the implementation of condition monitoring solutions plays an important role in Maintenance Management. This work aims to present a development of a low-cost equipment prototype based on IoT (Internet of Things) concepts and technologies with the application of an ESP32 microcontroller and open-source platforms intending to monitor electrical and environmental data from an electrical panel, as well as using the concept of Big Data for the construction of a model for providing data for health prognosis and failure prediction of electrical equipment. Bench tests and sensor calibration were conducted to validate the consistency of sensor readings and for guarantee the measurement in the database. For installation in an industrial environment, thresholds were set for each variable in a monitoring software which allows for sending alerts, identifying measurement deviations and composing maintenance/performance indicators based on electric current, voltage, humidity, temperature, pressure, active power, reactive power and power factor, besides opening/closing some equipment and physical MCC doors.
Keywords: maintenance management; internet of things